Development of IoT Household Appliances Asset Tracking System - Lumbwe , Mathias Mwansa; Nyirenda, Mayumbo (Proceedings of International Conference for ICT (ICICT) - Zambia, 2025)
This research presents an IoT-based asset tracking system for household electronics, addressing the high theft rates and low recovery prospects of valuable appliances by leveraging affordable IoT devices with GPS technology for real-time monitoring, theft detection, and last-known-location reporting. The prototype, built using a Java Spring Boot server, supports multiple GPS protocols (GT06, Teltonika, Astra Telematics) with robust packet parsing and geolocation decoding, validated through mixed-methods qualitative stakeholder analysis and quantitative field testing, which demonstrated high accuracy and reliability despite minor data integrity issues. The study confirms the feasibility and effectiveness of extending IoT tracking to households, proposing a tiered deployment strategy to match tracker capabilities to asset value for cost-efficiency, with future work focusing on energy optimization and smart home integration.